Catalytic Conversion of Inert Carbohydrates into Platform Chemical 5‐Hydroxymethylfurfural Using Arylboronic Acids. Issue 11 (5th November 2013) - Lukamto, Daniel H.; Wang, Peng; Loh, Teck‐Peng
<x xml:space="preserve">Abstract</x> Looking forward: As fossil fuels deplete, 5‐hydroxymethylfurfural (HMF) will play an important role in securing future energy and chemical feedstock needs as it is obtainable from renewable resources such as glucose and cellulose. We report a group of nonmetal Lewis‐acid arylboronic acids that catalyse the formation of HMF in 3‐ethyl‐1‐methyl‐3 H‐imidazol‐1‐ium chloride ([EMIM]Cl) from glucose and cellulose. EWG=electron‐withdrawing group.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>